The spindle pole body component Spc97p interacts with the γ‐tubulin of Saccharomyces cerevisiae and functions in microtubule organization and spindle pole body duplication - Knop, Michael; Pereira, Gislene; Schiebel, Elmar (The EMBO journal, 1997)
Previously, we have shown that the gamma-tubulin Tub4p and the spindle pole body component Spc98p are involved in microtubule organization by the yeast microtubule organizing centre, the spindle pole body (SPB). In this paper we report the identification of SPC97 encoding an essential SPB component that is in association with the SPB substructures that organize the cytoplasmic and nuclear microtubules. Evidence is provided for a physical and functional interaction between Tub4p, Spc98p and Spc97p: first, temperature-sensitive spc97(ts) mutants are suppressed by high gene dosage of SPC98 or TUB4. Second, Spc97p interacts with Spc98p and Tub4p in the two-hybrid system. Finally, immunoprecipitation and fractionation studies revealed complexes containing Tub4p, Spc98p and Spc97p. Further support for a direct interaction of Tub4p, Spc98p and Spc97p comes from the toxicity of strong SPC97 overexpression which is suppressed by co-overexpression of TUB4 or SPC98. Analysis of temperature-sensitive spc97(ts) alleles revealed multiple spindle defects. While spc97-14 cells are either impaired in SPB separation or mitotic spindle formation, spc97-20 cells show an additional defect in SPB duplication. We discuss a model in which the Tub4p-Spc98p-Spc97p complex is part of the microtubule attachment site at the SPB.
Gesehen am 31.08.2017